Seductions of an Underdevelopment Trap : Systemic Impediments to Agricultural Reform in Russia - Gershenson, Dmitry (IMF Working Papers; Working Paper, 2002)
Despite ambitious agricultural reforms initiated by the federal government, inefficient and unprofitable producers predominate in post-Soviet Russia. However, in some regions a more robust restructuring has taken place. Observing two Russian regions-one with substantially restructured agricultural production, and one in which Soviet-style coordination predominates-we develop a model of the interactions between political and economic incentives that lead to these divergent outcomes. The model identifies region- and sector-specific characteristics that encourage some regional governments to maintain Soviet-style redistribution structures and make producers forsake more efficient outcomes as more costly, while encouraging other regions to pursue reform.